2006
DOI: 10.1038/sj.onc.1209787
|View full text |Cite
|
Sign up to set email alerts
|

Sustained mitotic block elicits DNA breaks: one-step alteration of ploidy and chromosome integrity in mammalian cells

Abstract: Following prolonged mitotic spindle disruption by microtubule poisons, mammalian cells delay their entry into anaphase, then progressively slip out of mitosis and become tetraploid. Normal cells then stop cycling before S-phase onset, but the mechanisms underlying this arrest are still unclear. Here we show that a double block prevents endo-reduplication. First, cells that exit mitosis without a functional microtubule network are driven toward G0. Reconstitution of the network unmasks a second block that relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 31 publications
4
54
1
Order By: Relevance
“…However, γH2A.X was never found in cells with high cyclin B1, showing absence of DSBs in G2 phase. These data indicate that DNA damage is generated during mitosis, in agreement with break formation after spindle disruption (10,11) and the mitotic origin of micronuclei (21). The lack of γH2A.X in G2 cells suggests that damage is eliminated during S phase.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…However, γH2A.X was never found in cells with high cyclin B1, showing absence of DSBs in G2 phase. These data indicate that DNA damage is generated during mitosis, in agreement with break formation after spindle disruption (10,11) and the mitotic origin of micronuclei (21). The lack of γH2A.X in G2 cells suggests that damage is eliminated during S phase.…”
Section: Resultssupporting
confidence: 60%
“…rarely found in sporadic tumors (5,7,8). In contrast, several lines of evidence implicate the mitotic spindle in DSB generation; genetic or drug-induced spindle abnormalities cause γH2A.X accumulation (10,11), γH2A.X levels in untreated cells correlate with numerical chromosome instability (9), and cancer cell lines with a CIN phenotype show numerous translocations close to centromeric regions (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was attributed to partial activation of caspase activity during a prolonged mitotic arrest. This rendered DNA fragmentation and a p53-mediated DNA damage response in post-slippage cells (Quignon et al 2007, Orth et al 2012. Work from the Shi Lab further showed that the DNA damage response pathway was primarily responsible for post-slippage apoptosis in a p53-dependent manner (Zhu et al 2014).…”
Section: Post-slippage Cell Death and Cytotoxic Drug Responsementioning
confidence: 99%